Pendampingan Membaca melalui Klinik Literasi: Upaya Mahasiswa Asistensi Mengajar dalam Meningkatkan Literasi Dasar di SDN 3 Selong: Penelitian - Dina Fadilah; Fania Saputri; Dewi Saputri; Nur Rahmatia; Raohon Hayati; M. Riki Mahesa Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Reading ability is a fundamental foundation for academic success in elementary school students; however, many lower grade students still experience reading difficulties. This study aims to describe the implementation and impact of the Literacy Clinic Program through student teaching assistance in improving basic literacy at SDN 3 Selong. The research approach uses qualitative descriptive method with case study design. The population includes students from grades 1 to 4 experiencing reading difficulties, lower grade teachers, and student teaching assistants. Sampling technique uses purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana with source and method triangulation. Results show that the Literacy Clinic Program implemented twice weekly with varied learning methods successfully improved students' reading ability in letter recognition, reading fluency, and reading comprehension. The program also fostered reading interest, increased student confidence, and changed learning behavior positively. In conclusion, the Literacy Clinic Program proved effective as an intervention model to improve basic literacy and can be adopted by other elementary schools with multi-stakeholder collaborative support from schools, higher education institutions, and families.